2013
DOI: 10.1080/14783363.2013.809941
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the antecedents that influence middle management employees' knowledge-sharing intentions in the context of total quality management implementations

Abstract: The purpose of this paper is to investigate the motivations that affect middle management employees' knowledge-sharing intentions in the context of total quality management (TQM) implementations of Taiwan's information technology (IT) industry. A research model was developed based on TQM implementations and the theory of reasoned action. Survey samples were collected from 395 middle management employees in 50 Taiwanese ISO 9001:2000-certified firms in the IT industry, providing support for the proposed model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…First, the research focused on the use of BE frameworks for TQM implementation (Calabrese & Corbò, 2015;Chuang et al, 2015;Metaxas & Koulouriotis, 2014).…”
Section: Research Trendsmentioning
confidence: 99%
“…First, the research focused on the use of BE frameworks for TQM implementation (Calabrese & Corbò, 2015;Chuang et al, 2015;Metaxas & Koulouriotis, 2014).…”
Section: Research Trendsmentioning
confidence: 99%
“…Chow and Chan (2008) and Tohidinia and Mosakhani (2010) found that employee attitudes and subjective norms related to knowledge sharing positively affected the intention to share knowledge. Chuang et al. (2015) showed that perceived ethics, attitude, and subjective norm of Taiwanese IT employees positively affected their willingness to engage in knowledge sharing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past 50 years, total quality management (TQM) has been broadly adopted by many firms Andrade, Mendes and Lourenço (2017); Aoun and Hasnan (2017); Chuang, Chen and Tsai (2015); Fernandes, Sampaio, Sameiro and Truong (2017); Fu, Chou, Chen and Wang (2015). Andrade et al (2017) analyzed the differences in the perception of empowerment between TQM-based firms and non-TQM-based firms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition; the findings indicated that people-based management influenced on employees' innovation skills and there was not the relationship between employees' innovation skills and continuous improvement in Lebanese hospitals. Chuang et al (2015) examined the influence motivations on middle management employees᾽ knowledge-sharing intentions in the implementation of TQM in 395 middle management employees in 50 Taiwanese ISO 9001:2000-certified firms. The findings of this paper found that there were the significant relationships between self-efficacy, subjective norms, perceived ethics and attitudes towards knowledge sharing in the implementations of TQM.…”
Section: Introductionmentioning
confidence: 99%